THE REPRESENTATION OF WOMEN IN DIGITAL CULTURE: A SEMIOTIC ANALYSIS OF THE EPISODES NOSEDIVE AND JOAN IS AWFUL OF BLACK MIRROR - Vieira, Alcioni Galdino; Silva, Acauã Galdino Vieira (Seven Editora, 2025)
This article proposes a semiotic analysis of the representation of women in technomedia environments, based on the episodes Nosedive (2016) and Joan Is Awful (2023) from the Black Mirror series. The research is based on Charles Sanders Peirce’s theory of signs and engages with feminist and media culture studies, with the aim of examining how visual, narrative and performative signs participate in the discursive constructions of the feminine under conditions of algorithmic surveillance, hyperexposure and automation of the image. In Nosedive, the social performance of a protagonist conditioned by a digital reputation system is analyzed, whose visual and behavioral signs reveal a logic of normative control disguised by an aesthetic of compulsory well-being and performed affectivity. This mandatory positivity, articulated with ranking and public validation systems, operates as an instrument of subjective docility and masking of coercive structures under the appearance of individual choice. In Joan Is Awful, we can see the capture of experiences by narrative algorithms, which convert the character’s identity into an object of simulation and consumption, removing her control over her own image, in favor of entertainment. The articulation between Peircean semiotics and feminist criticism allows us to interpret how digital culture reconfigures the representations of women through ambiguous sign processes, regulated by social conventions and technical devices. The comparison between the episodes highlights transformations in the modes of audiovisual construction of female identities and points to narrative strategies that suggest possible ruptures in the face of the technological domestication of the image of women. DOI: https://doi.org/10.56238/sevened2025.026-005